Composition and diversity of the vegetation in four sites of Mexico’s Northeast - Ramírez-Lozano, Roque G.; Domínguez-Gómez, Tilo G.; González-Rodríguez, Humberto; Cantú-Silva, Israel; Gómez-Meza, Marco V.; Sarquís-Ramírez, Jorge I.; Jurado, Enrique (Instituto de Ecología, A.C., 2013)
During the summer of 2007, a study of the status of trees and woody vegetation was performedat four sites, in the state of Nuevo Leon, Mexico. Site one (S1, Bosque Escuela) was located at 1600 melevation in Iturbide county. Sites S2 (Crucitas, 550 m), S3 (Campus, 350 m) and S4 (Cascajoso, 300m) were located in Linares county. In each site, 10 random plots (10 m x 10 m) were laid out, and relativeabundance, relative dominance and relative frequency were estimated. In addition, dasometric parameterssuch as height and crown diameter were determined. Plant diversity was estimated by the Shannon-Wiener index, and similarity between sites was calculated using the Jaccard index. A total of 13710 individual plants belonging to 28 familieswere registered. Leguminosae had thehighest number of species (10) followedby Fagaceae (4), Rutaceae (4), Euphorbiaceae(3), Oleaceae (3), Cupressaceae(3), Rhamnaceae (2) and Verbenaceae(2). Eighteen families included only onespecies. The site with higher and lowerShannon index was Cascajoso (2,08)and Bosque Escuela (1,64), respectively.The Jaccard index showed similarityamong species only among S2, S3 andS4 sites. The plant species more frequentwere: in S1 Quercus canbyi, Pinus pseudostrobusand Rhus pachyrranchys(11,9%); in S2 Havardia pallens (9,9%);in S3 Havardia pallens and Forestieraangustifolia (9,8%) and in S4 Acacia rigidula,Cordia boissieri and Karwinskiahumboldtiana (9,8%). S2 and S3 werethe sites with the greatest species diversity,perhaps as a result of higher rainfall.